The Strength Of Evidence Of Invoice Bonus As A Debt Binding Agreement - Rosita Nainggolan; Christian Daniel Hermes; Humala Sitinjak (IHSA Institute, 2022)
The agreement stated in the contract becomes a law for the parties who make it. What becomes a problem is when the agreement of the parties is only based on an invoice, which is known that the invoice is only proof of payment, as well as the amount of contents and the name of the goods on implementation of buying and selling, while the cooperation agreement on buying and selling is only done verbally. No one can prove that there were provisions in the agreement. It's just that the sale and purchase of the goods has taken place with the receipt of an invoice signed by the buyer as the recipient of the goods. This study analyzes data qualitatively. The method of approach to this research is normative. Source of data used secondary data. Data collection tools used with documentation studies. The location of the research implementation is in Pematangsiantar. The strength of an invoice receipt as a bond for accounts payable is a receipt as proof that there has been a sale and purchase of goods between the purchaser of production goods and the distributor as a supplier of production goods. So that the bill of invoice has the strength of evidence that the goods were received by the shop at the price according to the agreement and the distributor holds evidence that the goods have been received and the evidence is still in debt or paid for the payment for the goods.